A New Fe (III)-Selective Membrane Electrode Based on Fe (II) Phthalocyanine - Ozer, Tugba; Isildak, Ibrahim (KOREAN ELECTROCHEMISTRY SOC, 2019)
A new miniaturized all solid-state contact Fe (III)-selective PVC membrane electrode based on Fe (II) phthalocyanine as a neutral carrier was described. The effects of the membrane composition and foreign ions on the electrode performance was investigated. The best performance was obtained with a membrane containing 32% poly (vinyl chloride), 64% dioctylsebacate, 3% Fe (II) phthalocyanine, and 1% potassium tetrakis (p-chlorophenyl) borate. The electrode showed near Nernstian response of 26.04 +/- 0.95 mV/decade over the wide linear concentration range 1.0 x 10(-6) to 1.0 x 10(-1) M, and a very low limit of detection 1.8 +/- 0.5 x 10(-7) M. The potentiometric response of the developed electrode was independent at pH 3.5-5.7. The lifetime of the electrode was approximately 3 months and the response time was very short (< 7 s). It exhibited excellent selectivity towards Fe (III) over various cations. The miniaturized all solid-state contact Fe (III)-selective membrane electrode was successfully applied as an indicator electrode for the potentiometric titration of 1.0 x 10(-3) M Fe (III) ions with a 1.0 x 10(-2) M EDTA and the direct determination of Fe (III) ions in real water samples.
Keywords: PVC Membrane; Ion Selective Electrode; Fe (III); Phthalocyanine; MULTIWALLED CARBON NANOTUBES; ION-SELECTIVE ELECTRODES; POTENTIOMETRIC SENSOR; FLOW-INJECTION; IRON; SEAWATER; ACID; IRON(III); Electrochemistry